2004
DOI: 10.1080/01926230490431493
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity of SCH 351591, a Novel Phosphodiesterase-4 Inhibitor, in Cynomolgus Monkeys

Abstract: SCH351591, a novel phosphodiesterase-4 inhibitor under investigation as a potential therapeutic for asthma and chronic obstructive pulmonary disease (COPD), was evaluated in a 3-month rising-dose study in Cynomolgus monkeys. Four groups, containing four monkeys/sex, received vehicle control or rising doses up to 12, 24, or 48 mg/kg of SCH351591 daily. Although initial exposure produced clinical signs of emesis, reduced food intake, and reduced body weight, tachyphylaxis to the emesis allowed dose escalation up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 64 publications
2
46
0
Order By: Relevance
“…PDE 4 inhibitors have been shown to cause arteritis and vasculitis (inflammation of the arteries and vessels) in rats (Langle et al, 1994;Larson et al, 1996; http://www.fda.gov/ohrms/ dockets/ac/03/transcripts/3976T1.doc; Mecklenburg et al, 2006) and minipigs (Vogel et al, 1999). This finding was demonstrated more recently in cynomolgus monkeys, which was the first observation using this class of compounds in nonhuman primates (Losco et al, 2004). Recent data provided further evidence for inflammatory implications of PDE 4 inhibitors.…”
mentioning
confidence: 65%
“…PDE 4 inhibitors have been shown to cause arteritis and vasculitis (inflammation of the arteries and vessels) in rats (Langle et al, 1994;Larson et al, 1996; http://www.fda.gov/ohrms/ dockets/ac/03/transcripts/3976T1.doc; Mecklenburg et al, 2006) and minipigs (Vogel et al, 1999). This finding was demonstrated more recently in cynomolgus monkeys, which was the first observation using this class of compounds in nonhuman primates (Losco et al, 2004). Recent data provided further evidence for inflammatory implications of PDE 4 inhibitors.…”
mentioning
confidence: 65%
“…However, preclinical safety evaluations have indicated that PDE-4i induce vascular lesions, primarily in the mesenteric arteries of rats and in the coronary arteries of dogs, pigs, and monkeys (Hanton et al 2008;Heaslip et al 1994;Losco et al 2004;Zhang et al 2008). It is not known whether similar effects would be observed in humans.…”
Section: Introductionmentioning
confidence: 98%
“…Depending on the drug and duration of exposure, a mixed perivascular inflammatory cellular response can be observed. Perivascular fibrosis with intimal and medial hypertrophy is noted chronically (Losco et al 2004). Fulminant lesions can be observed as soon as 12 hr (Zhang et al, 2002a), but more typically several days of dosing are required to induce the full spectrum of morphologic changes (Zhang et al 2008).…”
Section: Preclinical Divi Associated With Small Moleculesmentioning
confidence: 99%
“…DIVI lesions associated with vasoactive compounds are very rare in the mouse but have been observed commonly in rats following treatment with phosphodiesterase (PDE) 3 and 4 inhibitors, adenosine receptor agonists, dopaminergic agonists, endothelin receptor antagonists, angiotensin, bradykinin, a-adrenergic agonists, and K ir channel antagonists (Herman et al 1989;Johansson 1981;W. Kerns et al 2005;Losco et al 2004;Mikaelian et al 2014).…”
Section: Preclinical Divi Associated With Small Moleculesmentioning
confidence: 99%